Conflict prevention by Bayesian persuasion - Raphaela Hennigs (Journal of Public Economic Theory, 2021)
Drawing upon the Bayesian persuasion literature, I show that a mediator can provide conflicting parties strategically with information to decrease the ex-ante war probability. In a conflict between two parties with private information about military strength, the mediator generates information about each conflicting party's strength and commits to sharing the obtained information with the respective opponent. The conflicting parties can be convinced not to fight each other. The conflicting parties benefit from mediation, as the ex-ante war probability is reduced. The benefit is taken up by weak conflicting parties. This benefit is larger when war is costlier and when the war probability absent mediation is higher.
Keywords: 330